2023
DOI: 10.1002/pon.6087
|View full text |Cite
|
Sign up to set email alerts
|

Understanding social network support, composition, and structure among cancer caregivers

Abstract: Objective: We examined the social network support, composition, and structure of pediatric cancer caregivers. Methods:We used a self-report survey to collect egocentric social network data from 107 caregivers of pediatric cancer patients and calculated descriptive statistics to examine cancer-related support network composition, function, and structure.We then ran logistic regressions to examine the relationships between network characteristics and overall satisfaction with social support.Results: Family membe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…This is in line with our expectations based on social role theory [42] and the gendered and familial nature of caregiving [35]. Focusing primarily on family had partly been indicated before [16,17]. Adding to this, the average quality of the network, in terms of contact frequency and closeness, did not change among inside caregivers.…”
Section: Network Changes Among Informal Carerssupporting
confidence: 89%
See 2 more Smart Citations
“…This is in line with our expectations based on social role theory [42] and the gendered and familial nature of caregiving [35]. Focusing primarily on family had partly been indicated before [16,17]. Adding to this, the average quality of the network, in terms of contact frequency and closeness, did not change among inside caregivers.…”
Section: Network Changes Among Informal Carerssupporting
confidence: 89%
“…However, longitudinal research from Germany found an increased network size among informal caregivers [3]. Mostly, family members were found to be a key part of the social network [16, 17]. Yet, there was also evidence from Iran and China of small networks with fewer immediate family members than expected [17, 18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, coworkers and neighbors can offer seemingly small but important support, such as flexibility in scheduling meetings or helping with yard maintenance, that frees up caregiver time and mental load. Research on non-biological/legal family support and the importance of broader social networks in caregiving is limited but growing [ 35 , 36 , 37 ]; future work can elucidate how caregivers can best leverage this support.…”
Section: Discussionmentioning
confidence: 99%
“…We asked caregivers to report on their perceptions of their immediate social environments using a personal network approach to measure extended networks, including caregivers' own network ties and supportive ties to the older adults to whom they provide care, including other caregivers in the network. This approach has been used to investigate social networks of small samples of caregivers of older adults (Friedman & Kennedy, 2021) in the United States and internationally (Llopis Cañameras, 2015; Rodríguez‐Madrid et al, 2018) as well as caregivers of pediatric cancer patients (Bouchard et al, 2023). This approach is in contrast to an approach that measures social networks from multiple informat reports of connections among caregivers within a closed community, such as families, assisted living communities, or those attending local adult daycare centers (Ashida et al, 2018; Koehly et al, 2015; Marcum et al, 2018).…”
Section: Introductionmentioning
confidence: 99%